Upper water column nitrification processes and the implications of euphotic zone nitrification for estimates of new production - Grundle, Damian Shaun (2012)
I used a specific inhibitor approach to systematically measure NH4+ oxidation rates through the euphotic zone of three distinct oceanographic regimes. Study sites included Saanich Inlet, a highly productive British Columbia fjord, the Line P oceanographic transect in the NE subarctic pacific, and the Bermuda Atlantic Time-series Study (BATS) station in the oligotrophic, sub-tropical Sargasso Sea. Nitrate uptake rates were also measured at select stations on a number of research cruises. NH4+ oxidation rates were found to proceed throughout the euphotic zone in each of my study regions, and, overall, euphotic zone NH4+ oxidation rates ranged from undetectable to 203 nmol L-1 d-1. A general characterization of the rates observed in each of my study regions shows that euphotic zone NH4+ oxidation rates were typically highest in Saanich Inlet, intermediate along Line P, and lowest at BATS. The observation that NH4+ oxidation occurred throughout the euphotic zone in each of my study regions was in contrast to the traditional assumption of no euphotic zone nitrification, and it should now be considered a ubiquitous process in the euphotic regions of the ocean. Results found that euphotic zone nitrification could have potentially supported, on average, 15, 53 and 79% of the phytoplankton NO3- requirements in Saanich Inlet, and along Line P and at BATS, respectively, and this underscores the need for a major re-evaluation of the new production paradigm. Light, substrate concentrations, and potentially substrate supply rates were all found to play a role in regulating NH4+ oxidation, albeit to varying degrees, and I discuss the influence that each of these variables may have had on controlling NH4+ oxidation rates at regionally specific scales in Chapters 2 (Saanich Inlet), 3 (Line P) and 4 (BATS). Finally, a cross study-region comparison of results showed that the relative degree by which new production estimates were reduced, when euphotic zone nitrification was taken into consideration, decreased exponentially as ...